Palmitic acid reduces LDLR-dependent uptake of macrophage-derived extracellular vesicles by hepatoma cells - Bootsakorn Boonkaew; Nantawat Satthawiwat; Bianca C. Pachane; Lucy M. Brett; Pisit Tangkijvanich; Chaiyaboot Ariyachet (Non-coding RNA Research)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is characterized by a complicated interaction of lipotoxicity and inflammation in the liver, yet the mechanisms linking these phenomena remain incompletely understood. In this study, we investigated the mechanistic uptake of extracellular vesicles (EVs) derived from macrophages into palmitic acid (PA)-induced lipotoxic hepatoma cells. By co-culturing macrophages with lipotoxic Huh7 cells in a transwell system, we demonstrated that PA-treated Huh7 cells exhibited impaired uptake of macrophage-derived EVs. Compared with control Huh7 cells, PA-treated Huh7 cells presented a reduction in the expression of macrophage-derived microRNA-223 (miR-223) after co-culture, accompanied by an increase in the expression of miR-223 target genes. Further analysis revealed that upon PA treatment, the expression of low-density lipoprotein receptor (LDLR) in Huh7 cells and EV uptake activity were simultaneously diminished. Gain- and loss-of-function experiments of LDLR in Huh7 cells revealed a crucial role of LDLR in facilitating EV uptake. Mechanistically, we elucidated that PA induced endoplasmic reticulum stress and subsequently stimulated proprotein convertase subtilisin/kexin type 9 (PCSK9)-mediated LDLR degradation. Administration of a PCSK9 inhibitor rescued LDLR levels and increased EV uptake in PA-treated Huh7 cells from macrophages. Moreover, we found that the uptake of macrophage-derived EVs lacking apolipoprotein E (ApoE) by Huh7 cells was lower than that of control EVs, highlighting the role of ApoE as a facilitator of EV transfer from macrophages into Huh7 cells. Overall, our study highlights the intricate mechanisms underlying EV-mediated communication between macrophages and Huh7 cells during lipotoxicity and provides insight into the development of EV-based therapies for MASLD.